Aluminum hydroxide filled hydrocarbon resin for copper-clad plate and preparation method thereof

By introducing aluminum hydroxide into the hydrocarbon resin and performing specific chemical modification, the problem of insufficient heat resistance, flame retardancy and peel strength of the hydrocarbon resin when preparing high-frequency copper clad plates is solved, and the excellent heat resistance and flame retardancy of the material are achieved.

CN119775646AActive Publication Date: 2025-04-08JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510067238.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-08
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

When preparing high-frequency copper clad plates, hydrocarbon resins have problems such as insufficient rigidity, low strength, poor heat resistance, low peel strength and poor flame retardant performance, which is difficult to meet the requirements of high-frequency electronic information transmission.

Method used

By introducing aluminum hydroxide into the hydrocarbon resin and through specific chemical reactions and modification processes, aluminium hydroxide-filled hydrocarbon resin is formed to improve its heat resistance and flame retardant properties.

Benefits of technology

The excellent heat resistance and flame retardant properties of aluminum hydroxide-filled hydrocarbon resin are achieved, the mechanical properties and thermal stability of the material are enhanced, and the peel strength and fire resistance of the copper clad plate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244624790000081
    Figure BDA0005244624790000081
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad plates, in particular to aluminum hydroxide filled hydrocarbon resin for a copper-clad plate and a preparation method thereof. The aluminum hydroxide filled hydrocarbon resin is prepared from the following components in parts by weight: 80 to 100 parts of epoxidized 1, 2-polybutadiene, 20 to 30 parts of aluminum hydroxide, 10 to 15 parts of boron nitride, 12 to 18 parts of a curing agent, 0.1 to 0.3 part of a curing accelerator and 90 to 110 parts of a solvent. By mixing epoxidized 1, 2-polybutadiene, aluminum hydroxide and boron nitride and combining the combined action of various auxiliaries, the prepared aluminum hydroxide filled hydrocarbon resin has excellent heat resistance and flame retardance, so that the service life of a copper-clad plate is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper clad laminates, in particular to an aluminum hydroxide filled hydrocarbon resin for copper clad laminates and a preparation method thereof. Background Art

[0002] With the continuous development of electronic communication technology, high-frequency electronic information transmission has also put forward higher requirements for copper clad laminates. Hydrocarbon resin is considered to be an ideal material for preparing high-frequency copper clad laminates due to its excellent dielectric properties and comprehensive performance. However, the flexibility and non-polar carbon chain structure of hydrocarbon resins lead to problems such as insufficient rigidity, low strength, poor heat resistance and low peel strength of the cured product, which limit the application of hydrocarbon resins. At the same time, hydrocarbon resins have poor flame retardant properties and are easily affected by flames, producing harmful gases and smoke, making it difficult to meet the flame retardant requirements of high-frequency electronic information transmission for copper clad laminates.

[0003] Therefore, we propose an aluminum hydroxide filled hydrocarbon resin for copper clad laminate and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a hydrocarbon resin filled with aluminum hydroxide for copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing aluminum hydroxide filled hydrocarbon resin for copper clad laminate comprises the following steps:

[0007] Step S1: 1,2-polybutadiene, a photoinitiator and 1-thioglycerol are uniformly mixed, and irradiated with ultraviolet light to obtain hydroxylated 1,2-polybutadiene;

[0008] Step S2: uniformly mixing hydroxylated 1,2-polybutadiene, epichlorohydrin and tetrabutylammonium bromide, heating to 65-75° C., reflux reaction for 3-4 hours, cooling to 45-55° C., adding sodium hydroxide solution, continuing reaction for 3-4 hours, filtering, washing and distilling under reduced pressure to obtain epoxidized 1,2-polybutadiene;

[0009] Step S3: Evenly mix epoxidized 1,2-polybutadiene and solvent, raise the temperature to 50-60° C., add aluminum hydroxide, boron nitride, curing agent, and curing accelerator, and evenly mix to obtain aluminum hydroxide-filled hydrocarbon resin.

[0010] In the above technical scheme, a hydroxyl group is introduced through a thiol-ene click chemical reaction between the side chain vinyl double bond of 1,2-polybutadiene and the thiol group in 1-thioglycerol to generate hydroxylated 1,2-polybutadiene; the hydroxylated 1,2-polybutadiene is then reacted with epichlorohydrin to epoxidize the hydroxyl group to generate epoxidized 1,2-polybutadiene; finally, the epoxidized 1,2-polybutadiene is mixed with aluminum hydroxide and boron nitride, and combined with the combined action of a variety of additives, to prepare an aluminum hydroxide-filled hydrocarbon resin having excellent heat resistance and flame retardant properties.

[0011] Furthermore, in step S1, the mass ratio of 1,2-polybutadiene, photoinitiator and 1-thioglycerol is 1:(0.01-0.03):(1-2).

[0012] Furthermore, in step S1, the photoinitiator is 2-hydroxy-2-methylpropiophenone.

[0013] Furthermore, the process conditions of ultraviolet irradiation in step S1 are: irradiation with 360-380nm ultraviolet light for 5-7h, irradiation intensity of 20-25mW / cm 2 .

[0014] Furthermore, in step S2, the mass ratio of hydroxylated 1,2-polybutadiene to epichlorohydrin and tetrabutylammonium bromide is 1:(2-3):(0.01-0.03).

[0015] Furthermore, the concentration of the sodium hydroxide solution in step S2 is 40-45 wt %, and the amount thereof is 3-4 times the mass of the hydroxylated 1,2-polybutadiene.

[0016] Furthermore, the aluminum hydroxide filled hydrocarbon resin includes the following components by weight: 80-100 parts of epoxidized 1,2-polybutadiene, 20-30 parts of aluminum hydroxide, 10-15 parts of boron nitride, 12-18 parts of curing agent, 0.1-0.3 parts of curing accelerator, and 90-110 parts of solvent.

[0017] Furthermore, the aluminum hydroxide is modified, and the specific modification process is:

[0018] Step (1): Hexamethylenediaminetetramethylenephosphonic acid and deionized water are mixed evenly, aluminum hydroxide is added, the temperature is raised to 90-100° C., the reaction is carried out for 6-8 hours, the mixture is cooled to room temperature, and after filtering, washing and drying, compound A is obtained;

[0019] Step (2): Mix melamine and deionized water evenly, heat to 90-100° C., adjust the system pH to 5-6 with hydrochloric acid solution, add compound A, continue to react for 6-8 hours, filter, wash, dry, and cool to room temperature to obtain modified aluminum hydroxide.

[0020] In the above technical scheme, hexamethylenediaminetetramethylenephosphonic acid is reacted with aluminum hydroxide to introduce P-OH active groups on the surface of aluminum hydroxide, which is then reacted with melamine to introduce -NH2 active groups, which can further react with epoxidized 1,2-polybutadiene to form a network structure, thereby improving the thermal stability and flame retardancy of the material.

[0021] Furthermore, in the step (1), the mass ratio of hexamethylenediaminetetramethylenephosphonic acid to deionized water is 1:(25-30).

[0022] Furthermore, in step (1), the mass of aluminum hydroxide is 10-20% of the mass of hexamethylenediaminetetramethylenephosphonic acid.

[0023] Furthermore, in the step (2), the mass ratio of melamine to deionized water is 1:(25-30).

[0024] Furthermore, the concentration of the hydrochloric acid solution in step (2) is 1.0-1.2 mol / L.

[0025] Furthermore, in step (2), the mass of compound A is 0.3-0.5 times the mass of melamine.

[0026] Furthermore, the preparation method of the curing agent is as follows:

[0027] Evenly mix triethylenetetramine, diphenylvinylethoxysilane and tetrahydrofuran, raise the temperature to 70-80°C, react for 4-6 hours, and distill under reduced pressure to obtain a curing agent.

[0028] In the above technical scheme, a rigid benzene ring structure is introduced by allowing the amino group at one end of triethylenetetramine to undergo a Michael addition reaction with the double bond in diphenylvinylethoxysilane; the amino group at the other end can react with epoxidized 1,2-polybutadiene, thereby improving the mechanical properties and thermal stability of the material.

[0029] Furthermore, the mass ratio of triethylenetetramine to diphenylvinylethoxysilane and tetrahydrofuran is 1:

[0030] (1.7-1.8):(5-10).

[0031] Furthermore, the curing agent accelerator is 2-methylimidazole.

[0032] Furthermore, the solvent consists of 60-70 parts of toluene and 30-40 parts of xylene.

[0033] An application of aluminum hydroxide filled hydrocarbon resin for copper clad laminates comprises the following steps:

[0034] The glass fiber cloth is completely immersed in aluminum hydroxide filled hydrocarbon resin for 3-12 minutes, taken out, and baked at 150-180°C for 10-20 minutes to obtain a semi-cured sheet; 3-9 semi-cured sheets are stacked together to obtain a composite multi-layer sheet, and a copper foil is placed on the upper surface and the lower surface of the composite multi-layer sheet respectively, and a copper clad laminate is obtained through a lamination process.

[0035] Furthermore, the lamination process conditions are: lamination temperature 180-260° C., lamination pressure 2-5 MPa, and lamination time 3-7 h.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The invention discloses an aluminum hydroxide-filled hydrocarbon resin for copper clad laminates and a preparation method thereof. The side chain vinyl double bond of 1,2-polybutadiene undergoes a thiol-ene click chemical reaction with the thiol group in 1-thioglycerol to introduce a hydroxyl group to generate hydroxylated 1,2-polybutadiene; the hydroxylated 1,2-polybutadiene is then reacted with epichlorohydrin to epoxidize the hydroxyl group to generate epoxidized 1,2-polybutadiene; finally, the epoxidized 1,2-polybutadiene is mixed with aluminum hydroxide and boron nitride and combined with the combined action of a plurality of additives to prepare an aluminum hydroxide-filled hydrocarbon resin having excellent heat resistance and flame retardancy.

[0038] 2. The aluminum hydroxide-filled hydrocarbon resin for copper clad laminates of the present invention and the preparation method thereof form a three-dimensional network structure through a cross-linking reaction between the epoxy groups in the epoxidized 1,2-polybutadiene and the amino groups in the curing agent, thereby enhancing the mechanical properties and thermal stability of the material; at the same time, the epoxy groups in the epoxidized 1,2-polybutadiene can also react with the amino groups in the modified aluminum hydroxide, which can not only effectively improve the flame retardant properties of the material and make it have better fire resistance under high temperature conditions, but also further enhance the interface bonding between the materials, thereby improving the peel strength of the copper clad laminate. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In this example, 1,2-polybutadiene: average molecular weight 3×10 5, from Shanghai McLean Biochemical Technology Co., Ltd.; aluminum hydroxide: brand AH-1, particle size 5000 mesh, from Jiangyin Guangyuan Superfine Powder Co., Ltd.; boron nitride: hexagonal boron nitride, particle size 10-45μm, from Zhejiang Yamei Nano Technology Co., Ltd.; glass fiber cloth: specification 2116, thickness 0.08mm, gram weight 105g / m 2 , sourced from Guangzhou Hetaisi Composite Materials Co., Ltd.; copper foil: T2 copper, sourced from Shanghai Xinye Metal Products Co., Ltd.

[0041] In the following examples and comparative examples, 1 part is equal to 10 g.

[0042] Embodiment 1: A method for preparing a copper-clad laminate by filling hydrocarbon resin with aluminum hydroxide, comprising the following process:

[0043] Step S1: 80 parts of 1,2-polybutadiene, 0.8 parts of photoinitiator and 80 parts of 1-thioglycerol were mixed evenly and irradiated with 360nm ultraviolet light for 5 hours with an irradiation intensity of 20mW / cm 2 , to obtain hydroxylated 1,2-polybutadiene;

[0044] Step S2: 80 parts of hydroxylated 1,2-polybutadiene, 160 parts of epichlorohydrin and 0.8 parts of tetrabutylammonium bromide were mixed uniformly, the mixture was heated to 65° C., refluxed for reaction for 3 hours, cooled to 45° C., 240 parts of 40 wt% sodium hydroxide solution were added, the reaction was continued for 3 hours, and epoxidized 1,2-polybutadiene was obtained by filtering, washing and distilling under reduced pressure;

[0045] Step S3: 80 parts of epoxidized 1,2-polybutadiene, 60 parts of toluene and 30 parts of xylene are mixed evenly, the temperature is raised to 50° C., 20 parts of aluminum hydroxide, 10 parts of boron nitride, 12 parts of a curing agent and 0.1 parts of a curing accelerator are added and mixed evenly to obtain an aluminum hydroxide-filled hydrocarbon resin;

[0046] Aluminum hydroxide is modified, and the specific modification process is:

[0047] Step (1): 200 parts of hexamethylenediaminetetramethylenephosphonic acid and 5000 parts of deionized water are mixed evenly, 20 parts of aluminum hydroxide are added, the temperature is raised to 90° C., the reaction is performed for 6 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain compound A;

[0048] Step (2): 70 parts of melamine and 1750 parts of deionized water are mixed evenly, the temperature is raised to 90° C., the pH value of the system is adjusted to 5 with a 1.0 mol / L hydrochloric acid solution, 21 parts of compound A are added, the reaction is continued for 6 hours, and after filtering, washing, and drying, the mixture is cooled to room temperature to obtain modified aluminum hydroxide;

[0049] The preparation method of the curing agent is as follows:

[0050] 12 parts of triethylenetetramine, 20.4 parts of diphenylvinylethoxysilane and 60 parts of tetrahydrofuran were mixed evenly, heated to 70°C, reacted for 4 hours, and distilled under reduced pressure to obtain a curing agent;

[0051] An application of aluminum hydroxide filled hydrocarbon resin for copper clad laminates comprises the following steps:

[0052] The glass fiber cloth was completely immersed in aluminum hydroxide filled hydrocarbon resin for 3 minutes, taken out, and baked at 150°C for 10 minutes to obtain a semi-cured sheet; three semi-cured sheets were stacked together to obtain a composite multi-layer sheet, and a copper foil was placed on the upper surface and the lower surface of the composite multi-layer sheet respectively, and a copper clad laminate was obtained through a lamination process (lamination temperature 180°C, lamination pressure 2MPa, lamination time 3h).

[0053] Embodiment 2: A method for preparing a copper-clad laminate by filling hydrocarbon resin with aluminum hydroxide, comprising the following process:

[0054] Step S1: 90 parts of 1,2-polybutadiene, 1.8 parts of photoinitiator and 135 parts of 1-thioglycerol were mixed evenly and irradiated with 370nm ultraviolet light for 6 hours with an irradiation intensity of 22mW / cm 2 , to obtain hydroxylated 1,2-polybutadiene;

[0055] Step S2: 90 parts of hydroxylated 1,2-polybutadiene, 225 parts of epichlorohydrin and 1.8 parts of tetrabutylammonium bromide were mixed uniformly, the mixture was heated to 70°C, refluxed for reaction for 3.5 hours, cooled to 50°C, 315 parts of 42 wt% sodium hydroxide solution were added, the reaction was continued for 3.5 hours, and epoxidized 1,2-polybutadiene was obtained by filtering, washing and distilling under reduced pressure;

[0056] Step S3: 90 parts of epoxidized 1,2-polybutadiene, 65 parts of toluene and 35 parts of xylene are mixed evenly, the temperature is raised to 55° C., 25 parts of aluminum hydroxide, 12 parts of boron nitride, 16 parts of a curing agent and 0.2 parts of a curing accelerator are added and mixed evenly to obtain an aluminum hydroxide-filled hydrocarbon resin;

[0057] Aluminum hydroxide is modified, and the specific modification process is:

[0058] Step (1): 150 parts of hexamethylenediaminetetramethylenephosphonic acid and 4200 parts of deionized water were mixed evenly, 25 parts of aluminum hydroxide were added, the temperature was raised to 95° C., the reaction was performed for 7 hours, the mixture was cooled to room temperature, and the mixture was filtered, washed and dried to obtain compound A;

[0059] Step (2): 62.5 parts of melamine and 1750 parts of deionized water were mixed evenly, the temperature was raised to 95° C., the pH value of the system was adjusted to 5.5 with 1.1 mol / L hydrochloric acid solution, 25 parts of compound A were added, the reaction was continued for 7 hours, and after filtering, washing, and drying, the mixture was cooled to room temperature to obtain modified aluminum hydroxide;

[0060] The preparation method of the curing agent is as follows:

[0061] 16 parts of triethylenetetramine, 28 parts of diphenylvinylethoxysilane and 128 parts of tetrahydrofuran were mixed evenly, heated to 75°C, reacted for 5 hours, and distilled under reduced pressure to obtain a curing agent;

[0062] An application of aluminum hydroxide filled hydrocarbon resin for copper clad laminates comprises the following steps:

[0063] The glass fiber cloth was completely immersed in aluminum hydroxide filled hydrocarbon resin for 10 minutes, taken out, and baked at 160°C for 15 minutes to obtain a semi-cured sheet; 5 semi-cured sheets were stacked together to obtain a composite multi-layer sheet, and a copper foil was placed on the upper surface and the lower surface of the composite multi-layer sheet respectively, and a copper clad laminate was obtained through a lamination process (lamination temperature 220°C, lamination pressure 3MPa, lamination time 5h).

[0064] Embodiment 3: A method for preparing a copper-clad laminate by filling hydrocarbon resin with aluminum hydroxide, comprising the following process:

[0065] Step S1: 100 parts of 1,2-polybutadiene, 3 parts of photoinitiator and 200 parts of 1-thioglycerol were mixed evenly and irradiated with 380nm ultraviolet light for 7h with an irradiation intensity of 25mW / cm 2 , to obtain hydroxylated 1,2-polybutadiene;

[0066] Step S2: 100 parts of hydroxylated 1,2-polybutadiene, 300 parts of epichlorohydrin and 3 parts of tetrabutylammonium bromide are mixed uniformly, the mixture is heated to 75° C., refluxed for 4 hours, cooled to 55° C., 400 parts of 45 wt% sodium hydroxide solution are added, the reaction is continued for 4 hours, and epoxidized 1,2-polybutadiene is obtained by filtering, washing and distilling under reduced pressure;

[0067] Step S3: 100 parts of epoxidized 1,2-polybutadiene, 70 parts of toluene and 40 parts of xylene are mixed evenly, the temperature is raised to 60° C., 30 parts of aluminum hydroxide, 15 parts of boron nitride, 18 parts of a curing agent and 0.3 parts of a curing accelerator are added and mixed evenly to obtain an aluminum hydroxide-filled hydrocarbon resin;

[0068] Aluminum hydroxide is modified, and the specific modification process is:

[0069] Step (1): 150 parts of hexamethylenediaminetetramethylenephosphonic acid and 4500 parts of deionized water are mixed evenly, 30 parts of aluminum hydroxide are added, the temperature is raised to 100° C., the reaction is performed for 8 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain compound A;

[0070] Step (2): 60 parts of melamine and 1800 parts of deionized water are mixed evenly, the temperature is raised to 100° C., the pH value of the system is adjusted to 6 with a 1.2 mol / L hydrochloric acid solution, 30 parts of compound A are added, and the reaction is continued for 8 hours. After filtering, washing, and drying, the mixture is cooled to room temperature to obtain modified aluminum hydroxide;

[0071] The preparation method of the curing agent is as follows:

[0072] 18 parts of triethylenetetramine, 32.4 parts of diphenylvinylethoxysilane and 180 parts of tetrahydrofuran were mixed evenly, heated to 80°C, reacted for 6 hours, and distilled under reduced pressure to obtain a curing agent;

[0073] An application of aluminum hydroxide filled hydrocarbon resin for copper clad laminates comprises the following steps:

[0074] The glass fiber cloth was completely immersed in aluminum hydroxide filled hydrocarbon resin for 12 minutes, taken out, and baked at 180°C for 20 minutes to obtain a semi-cured sheet; 9 semi-cured sheets were stacked together to obtain a composite multi-layer sheet, and a copper foil was placed on the upper surface and the lower surface of the composite multi-layer sheet respectively, and a copper clad laminate was obtained through a lamination process (lamination temperature 260°C, lamination pressure 5MPa, lamination time 7h).

[0075] Comparative Example 1: The aluminum hydroxide-filled hydrocarbon resin includes the following components by weight: 80 parts of epoxidized 1,2-polybutadiene, 20 parts of aluminum hydroxide, 10 parts of boron nitride, 5 parts of curing agent, 0.1 parts of curing accelerator, and 90 parts of solvent; compared with Example 1, Comparative Example 1 reduces the amount of curing agent added, and other steps and processes are the same as Example 1.

[0076] Comparative Example 2: The aluminum hydroxide-filled hydrocarbon resin includes the following components by weight: 80 parts of 1,2-polybutadiene, 20 parts of aluminum hydroxide, 10 parts of boron nitride, 12 parts of curing agent, 0.1 parts of curing accelerator, and 90 parts of solvent; compared with Example 1, Comparative Example 2 replaces the epoxidized 1,2-polybutadiene with the same mass of 1,2-polybutadiene, and the other steps and processes are the same as Example 1.

[0077] Comparative Example 3: The aluminum hydroxide-filled hydrocarbon resin includes the following components by weight: 80 parts of epoxidized 1,2-polybutadiene, 50 parts of aluminum hydroxide, 10 parts of boron nitride, 12 parts of curing agent, 0.1 parts of curing accelerator, and 90 parts of solvent; compared with Example 1, Comparative Example 3 adds 50 parts of aluminum hydroxide, and the other steps and processes are the same as Example 1.

[0078] Comparative Example 4: A method for preparing a copper-clad laminate by filling hydrocarbon resin with aluminum hydroxide, comprising the following process:

[0079] Aluminum hydroxide is modified, and the specific modification process is:

[0080] Step (1): 150 parts of hexamethylenediaminetetramethylenephosphonic acid and 4200 parts of deionized water were mixed evenly, 25 parts of aluminum hydroxide were added, the temperature was raised to 95° C., the reaction was performed for 7 hours, the mixture was cooled to room temperature, and the mixture was filtered, washed and dried to obtain compound A;

[0081] Step (2): 62.5 parts of melamine and 1750 parts of deionized water were mixed uniformly, the temperature was raised to 95° C., the pH value of the system was adjusted to 5.5 with 1.1 mol / L hydrochloric acid solution, 6.25 parts of compound A were added, the reaction was continued for 7 hours, and after filtering, washing, and drying, the mixture was cooled to room temperature to obtain modified aluminum hydroxide;

[0082] Compared with Example 2, the mass of compound A in step (2) of Comparative Example 4 is 0.1 times the mass of melamine; the other steps are the same as Example 2.

[0083] Experiment: Take the copper clad laminates obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results:

[0084] The flame retardancy is determined according to the vertical combustion method of the UL-94 standard. The experimental steps are as follows: the copper clad laminate is cut into specimens of length 125 mm × width 13 mm × thickness 0.7 mm, the lower end is ignited, the combustion process of the specimen is recorded, and it is divided into different grades according to the performance: V-0 grade means that the material has no dripping sparks, the burning process time is less than 10 seconds, and the flame height is less than 50 mm; V-1 grade means that during the burning process, the flame height is less than 75 mm, the burning time does not exceed 30 seconds, and there is no obvious dripping sparks.

[0085] The heat resistance test was carried out using a lead-free soldering furnace. The experimental steps were as follows: the copper-clad laminate was cut into samples of 10 cm × 10 cm in size, placed in a 288°C tin furnace for 3 times, 10 seconds each time, and 120 seconds of tin immersion. The samples were taken out and cooled to room temperature. The surface of the samples was observed for bubble stratification, cracking, or fading, and the data was recorded.

[0086] The peel strength was measured according to IPC-TM-650 Version 2.4.8 "Copper Clad Laminate Peel and Impact Test Method". The experimental steps are as follows: the copper clad laminate was cut into strips of 100 mm long and 10 mm wide, the copper foil at one end of the strip was peeled off from the substrate by 12 mm, the peeled copper foil was clamped with a sample clamp, and the peel strength between the copper foil and the substrate was tested. During the test, the peel speed was set to 50 mm / min, the peel angle was 90°, and the peel distance was 25 mm.

[0087] Test Results

[0088]

[0089] According to the data in the above table, we can clearly draw the following conclusions:

[0090] 1. Compared with Examples 1-3, the heat resistance and peel strength of the products obtained in Examples 1, 2, and 3 are reduced, indicating that the performance of the aluminum hydroxide-filled hydrocarbon resin prepared by the present invention is affected by its components and their ratios. By selecting the components and ratios within the said range, materials with excellent thermal stability and mechanical properties can be prepared.

[0091] 2. Compared with Examples 1-3, the flame retardant properties of the product obtained in Comparative Example 4 are reduced. It can be seen that the performance of the modified aluminum hydroxide prepared by the present invention is affected by the ratio of each reagent in its preparation process. By selecting a mass ratio within the said range, the prepared modified aluminum hydroxide has excellent flame retardant properties, thereby providing an excellent flame retardant effect for the copper clad laminate.

[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0093] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing aluminum hydroxide filled hydrocarbon resin for copper clad laminate, characterized in that: The steps include: Step S1: 1,2-polybutadiene, a photoinitiator and 1-thioglycerol are uniformly mixed, and irradiated with ultraviolet light to obtain hydroxylated 1,2-polybutadiene; Step S2: uniformly mixing hydroxylated 1,2-polybutadiene, epichlorohydrin and tetrabutylammonium bromide, heating to 65-75° C., reflux reaction for 3-4 hours, cooling to 45-55° C., adding sodium hydroxide solution, continuing reaction for 3-4 hours, filtering, washing and distilling under reduced pressure to obtain epoxidized 1,2-polybutadiene; Step S3: Evenly mix epoxidized 1,2-polybutadiene and solvent, raise the temperature to 50-60° C., add aluminum hydroxide, boron nitride, curing agent, and curing accelerator, and evenly mix to obtain aluminum hydroxide-filled hydrocarbon resin.

2. The method for preparing a copper-clad laminate with aluminum hydroxide filled with hydrocarbon resin according to claim 1, characterized in that: In the step S1, the mass ratio of 1,2-polybutadiene, photoinitiator and 1-thioglycerol is 1:(0.01-0.03):(1-2).

3. The method for preparing a hydrocarbon resin filled with aluminum hydroxide for copper clad laminate according to claim 1, characterized in that: The aluminum hydroxide filled hydrocarbon resin comprises the following components by weight: 80-100 parts of epoxidized 1,2-polybutadiene, 20-30 parts of aluminum hydroxide, 10-15 parts of boron nitride, 12-18 parts of curing agent, 0.1-0.3 parts of curing accelerator and 90-110 parts of solvent.

4. The method for preparing a copper-clad laminated board filled with aluminum hydroxide hydrocarbon resin according to claim 3, characterized in that: The aluminum hydroxide is modified, and the specific modification process is: Step (1): Hexamethylenediaminetetramethylenephosphonic acid and deionized water are mixed evenly, aluminum hydroxide is added, the temperature is raised to 90-100° C., the reaction is carried out for 6-8 hours, the mixture is cooled to room temperature, and after filtering, washing and drying, compound A is obtained; Step (2): Mix melamine and deionized water evenly, heat to 90-100° C., adjust the system pH to 5-6 with hydrochloric acid solution, add compound A, continue to react for 6-8 hours, filter, wash, dry, and cool to room temperature to obtain modified aluminum hydroxide.

5. The method for preparing a hydrocarbon resin filled with aluminum hydroxide for copper clad laminate according to claim 4, characterized in that: In the step (1), the mass of the aluminum hydroxide is 0.10-0.12 times the mass of hexamethylenediaminetetramethylenephosphonic acid.

6. The method for preparing a hydrocarbon resin filled with aluminum hydroxide for copper clad laminate according to claim 4, characterized in that: The mass of compound A in step (2) is 0.3-0.5 times the mass of melamine.

7. The method for preparing a hydrocarbon resin filled with aluminum hydroxide for copper clad laminate according to claim 3, characterized in that: The preparation method of the curing agent is as follows: Evenly mix triethylenetetramine, diphenylvinylethoxysilane and tetrahydrofuran, raise the temperature to 70-80°C, react for 4-6 hours, and distill under reduced pressure to obtain a curing agent.

8. A hydrocarbon resin filled with aluminum hydroxide for copper clad laminates prepared according to the preparation method according to any one of claims 1 to 7.

9. An application of aluminum hydroxide filled hydrocarbon resin for copper clad laminate, characterized in that: The following steps are involved: The glass fiber cloth is completely immersed in aluminum hydroxide filled hydrocarbon resin for 3-12 minutes, taken out, and baked at 150-180°C for 10-20 minutes to obtain a semi-cured sheet; 3-9 semi-cured sheets are stacked together to obtain a composite multi-layer sheet, and a copper foil is placed on the upper surface and the lower surface of the composite multi-layer sheet respectively, and a copper clad laminate is obtained through a lamination process.

10. The use of a high thermal conductivity hydrocarbon resin for copper clad laminate according to claim 9, characterized in that: The lamination process conditions are: lamination temperature 180-260° C., lamination pressure 2-5 MPa, and lamination time 3-7 h.

Citation Information

Patent Citations

  • Epoxy resin composition as well as prepreg and metal-foil-clad laminated board manufactured by using same

    CN102226033A

  • Flame-retardant hydrocarbon resin for high-frequency copper-clad plate and preparation method thereof

    CN116656084A

  • Flame retardant as well as preparation method and application thereof

    CN117430630A

  • Polyphenyl ether modified hydrocarbon resin composition and application thereof in copper-clad plate

    CN117511233A

  • Environment-friendly reliable halogen-free copper-clad plate and preparation process thereof

    CN117549630A